N-succinyl chitosan preparation, characterization, properties and biomedical applications: A state of the art review - Bashir, S.; Teo, Y.Y.; Ramesh, S.; Ramesh, K.; Khan, A.A. (Walter de Gruyter GmbH, 2015)
N-succinyl chitosan (NSC) remains a promising chitosan derivative to develop targeted drug delivery, wound dressings, and tissue engineering systems. All these systems are important in life sciences. NSC is an amphiprotic derivative obtained from the N-acylation of chitosan. NSC exhibits extraordinary biocompatibility, significantly increased aqueous solubility in acidic and basic media without affecting the biological properties, appreciable transfection efficiency, and the ability to stimulate osteogenesis. NSC shows enhanced bioavailability, which highlights its potential applications in the biomedical field. This review briefly introduces chitosan, including its limitations as a biomaterial, and modifications of chitosan with a particular focus on acylation, along with a comprehensive overview of the synthesis, characterization, properties, biodistribution, and toxicological/biopharmaceutical profile of NSC. Furthermore, it extensively surveys current state-of-the-art NSC-based formulations for drug delivery with special emphasis on protein delivery, anti-cancer activity in the colon, as well as nasal and ophthalmic targeted gene/drug delivery. Moreover, it discusses NSC-based biomaterial applications in articular, adipose, and bone tissue engineering. In addition, it describes recent contributions of NSC-based hydrogels in wound dressings along with a brief account of drug delivery in combination with tissue engineering. Finally, it presents potential current challenges and future perspectives of NSC-based formulations in the biomedical field.